4CPS-036 Pharmaceutical interventions in a small hospital. (24th March 2020) - Jimenez, L; Lobo-Leon, E; Puivecino-Moreno, C; Gazquez-Perez, R; Varas-Perez, A
Abstract : Background and importance: One of the functions of a pharmacist is to validate the prescribed treatment by the doctor, taking into account efficacy, safety, adequacy and cost. Aim and objectives: To analyse pharmaceutical interventions (PI) in prescribed treatment in a 115 bed hospital, and to quantify the degree of acceptance. Material and methods: This descriptive study included patients with an antibiotic prescription whose PI were analysed over a period of 11 months (2018 and 2019). The collected data were: demographic data, antibiotic treatment and indication, duration of treatment, comorbidities and abnormal analytical values (glomerular filtrate, potassium level, C reactive protein), type of PI and acceptance rate of PI. PI were classified as: actions on efficacy, actions on safety, actions on adequacy and actions on cost. The acceptance rate of the PI was detected based on modifications to the medical prescription according to the recommendations. The pharmaceutical recommendations were made through daily assessments of the patient's history or talking by phone with the physician. Results: A total of 438 patients were studied and a PI was made in 1 of 3 patients (163 PI). The interventions were made in antibiotic and non-antibiotic prescriptions. Actions on efficacy: antimicrobial change after antibiogram (11%), antimicrobial inadequate posology (3%) and adding an antibiotic to get a broad antibacterial spectrum (3%). Actions on safety: dose adjustment due to renal failure (15%), dose adjustment due to adverse reaction (0.6%), suspending the drug due to an adverse reaction, contraindication or interaction (4%), suspending the antibiotic due to inadequate duration (20%), inadequate posology (2.4%), therapeutic duplicity (4%), actions on potassium as monitoring levels, increase or decrease in potassium dose (2.4%) and other (antithrombotic prophylaxis and monitoring nephrotoxicity by aminoglycosides (1.8%)). Actions on adequacy and cost: change to oral administration (24%). A total of 58% (94/163) of PI were accepted. Most PI not accepted (40/69) were recommendations about change to oral administration or suspending the antibiotic. The reasons for non-acceptance were clinical deterioration or the patient was discharged. Conclusion and relevance: More than half of the pharmaceutical interventions resulted in a change in the medical prescription according to the recommendation. Pharmaceutical validation ensures safety in the hospitalisation process and represents an improvement in quality of care. References and/or acknowledgements: No conflict of interest.